Two New Records of Wild Bananas (Musa balbisiana and Musa itinerans) from Sulawesi - Sulistyaningsih, Lulut Dwi; Megia, Rita; Widjaja, Elizabeth Anita (UI Scholars Hub, 2014)
The diversity of wild banana species in Sulawesi was investigated based on the morphological characteristics of herbarium specimens collected in Sulawesi and deposited in the Herbarium Bogoriense, Bogor, Indonesia (BO). New specimens were collected from Central, North, South, and Southeast Sulawesi, and digital type specimens were also used in this study. The aim of this study was to describe the diversity of wild banana species in Sulawesi as most Musaceae specimens stored at BO have not been identified. By examinating 110 sheets of herbarium specimens, five species of Musa, including two infraspecific taxa of M. acuminata housed in Sulawesi, were identified. Musa acuminata, M. celebica, and M. textilis were previously reported from Sulawesi. However, M. balbisiana and M. itinerans are two new records of wild banana species in Sulawesi. Identification keys, descriptions, distribution maps, and line-drawing illustrations of these two species are provided.